2007
DOI: 10.1177/1087057107299261
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Rheumatoid Arthritis Synovial Cells Treated with Antirheumatic Drugs

Abstract: Nonbiological therapeutics are frequently used for the treatment of patients with rheumatoid arthritis (RA). Because the mechanisms of action of these therapeutics are unclear, the authors aimed to elucidate the molecular effects of typical antirheumatic drugs on the expression profile of RA-related genes expressed in activated synovial fibroblasts. For reasons of standardization and comparability, immortalized synovial fibroblasts derived from RA (RASF) and normal donors (NDSF) were treated with methotrexate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 39 publications
4
41
0
1
Order By: Relevance
“…Subconfluent hMSCs were incubated with or without 10 Ϫ7 M dexamethasone for 1, 3, or 7 days, total RNA was isolated, and gene expression profiling with Affymetrix HG-U133 Plus 2.0 arrays was performed as described in ref. 21. Raw gene expression data were processed with the GCOS 1.2 software for signal calculation, and comparison analysis and cellular pathways were analyzed using statistical tools.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subconfluent hMSCs were incubated with or without 10 Ϫ7 M dexamethasone for 1, 3, or 7 days, total RNA was isolated, and gene expression profiling with Affymetrix HG-U133 Plus 2.0 arrays was performed as described in ref. 21. Raw gene expression data were processed with the GCOS 1.2 software for signal calculation, and comparison analysis and cellular pathways were analyzed using statistical tools.…”
Section: Methodsmentioning
confidence: 99%
“…S1 A-D). We analyzed the gene expression profile in these differentiating hMSCs using HG-U133 Plus 2.0 arrays consisting of 54,675 probe sets (21). Analysis of normalized data from three different donors revealed that ITGA5 expression was increased Ͼ2-fold in dexamethasone-treated hMSCs compared with that in untreated cells.…”
Section: Itga5mentioning
confidence: 99%
“…The only study available in the literature evaluated the effect of in vitro MTX treatment on RA and on control synovial fibroblasts, reporting that MTX reversed the modulated expression of genes related to apoptosis and cell adhesion in RA fibroblasts to the levels observed in control fibroblasts 28 . In our series, despite the small number of patients, we clearly observed modulation of genes implicated in apoptosis in MTX nonresponder patients when compared to responders.…”
Section: Discussionmentioning
confidence: 99%
“…Напротив, рост числа эрозий и величины сужения су-ставной щели (ССЩ) у серопозитивных больных РА в хо-де терапии МТ сопровождался увеличением экспрессии ММП9 и катепсина К в крови [16,17]. Кроме того, норма-лизация экспрессии генов, ассоциированных с ростом клеток и апоптозной активностью, также ранее наблюда-лась в присутствии МТ в культуре синовиальных фиб-робластов in vitro [18].…”
Section: Association Of Blood Gene Expressions In Rheumatoid Arthritiunclassified